2013
DOI: 10.1007/s00438-013-0748-6
|View full text |Cite
|
Sign up to set email alerts
|

Screening for long-lived genes identifies Oga1, a guanine-quadruplex associated protein that affects the chronological lifespan of the fission yeast Schizosaccharomyces pombe

Abstract: Schizosaccharomyces pombe and Saccharomyces cerevisiae are excellent model organisms to study lifespan. We conducted screening to identify novel genes that, when overexpressed, extended the chronological lifespan of fission yeast. We identified seven genes, among which we focused on SPBC16A3.08c. The gene product showed similarity to Ylr150w of S. cerevisiae, which has affinity for guanine-quadruplex nucleic acids (G4). The SPBC16A3.08c product associated with G4 in vitro and complemented the phenotype of an S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…We took advantage of the fact that the fission yeast genome encodes (SPBC725.10) and expresses a TSPO protein (here after called SpTSPO). Interestingly, SPBC725.10 is upregulated during nitrogen starvation and its deletion (strain ΔSPBC725.10) enhances sensitivity to the autophagy‐inducible drug rapamycin (Doi et al ., ), and its overexpression increases viability at the stationary growth phase (Ohtsuka et al ., ). We first confirmed by PCR that the SPBC725.10 locus was indeed disrupted in strain ΔSPBC725.10 (Figure a).…”
Section: Resultsmentioning
confidence: 97%
“…We took advantage of the fact that the fission yeast genome encodes (SPBC725.10) and expresses a TSPO protein (here after called SpTSPO). Interestingly, SPBC725.10 is upregulated during nitrogen starvation and its deletion (strain ΔSPBC725.10) enhances sensitivity to the autophagy‐inducible drug rapamycin (Doi et al ., ), and its overexpression increases viability at the stationary growth phase (Ohtsuka et al ., ). We first confirmed by PCR that the SPBC725.10 locus was indeed disrupted in strain ΔSPBC725.10 (Figure a).…”
Section: Resultsmentioning
confidence: 97%
“…TOR signaling has been suggested to play a role in S. pombe CLS (Roux et al ., ,b). A recent study confirmed that deletion of the Tor1 kinase indeed extended CLS (Ohtsuka et al ., ). Deletion of the Git3 glucose receptor (GPCR) has also been reported to extend CLS, further attesting the role of glucose signaling in CLS (Roux et al ., ).…”
Section: Aging Studies In Schizosaccharomyces Pombementioning
confidence: 97%
“…Most of these longevity genes have homologs in S. cerevisiae , which contribute to the characterization of their roles in S. pombe CLS. These studies have associated CLS with nutrient signaling (Roux et al ., ; Ohtsuka et al ., ; Chen & Runge, ; Roux et al ., ; Ito et al ., ), mitochondrial activity/maintenance (Zuin et al ., ; Roux et al ., ,b; Azuma et al ., ; Ohtsuka et al ., ; Stephan et al ., ), ROS production/stress resistance (Mutoh & Kitajima, ; Zuin et al ., ,b; Ohtsuka et al ., , ), proteasome activity/redistribution, autophagy (Takeda & Yanagida, ; Takeda et al ., ), and vacuolar function (Stephan et al ., ). Many of these factors also play a role in low glucose CR‐induced CLS extension (Ohtsuka et al ., ; Chen & Runge, ; Roux et al ., ; Zuin et al ., ,b).…”
Section: Aging Studies In Schizosaccharomyces Pombementioning
confidence: 99%
See 1 more Smart Citation
“…Cells were precultured in the Zn-depleted EMM for 13 h and then transferred into the Zn-depleted EMM and EMM containing 100 μM ZnSO 4 . After 2 h of cultivation, total RNA was prepared using the RNeasy Mini Kit (QIAGEN) as described previously (Ohtsuka et al 2013). Gene expression was analyzed by real-time PCR (Eco, Illumina) using primers AGCTCTGCTACTGTGAC TTG and CGTTGGGTCTGTTTTTGGTG (for zrt1), TGAT GCATGGGCGTATACAG and ATCCGGGAGTACATGTT GCT (for SPBC1348.06c), CCGCCCAGTTATGAAGCT GT and TACCATCGTCGAGAAGAGCT (for rgs1), and CTGCTTACCGCCCGAAAATA and TCAACATTTGCTT GCAGTTGGAG (for mei2), as described previously (Ohtsuka et al 2013).…”
Section: Northern Hybridization and Real-time Pcr Analysesmentioning
confidence: 99%